2019
DOI: 10.1002/brb3.1446
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐state brain entropy in right temporal lobe epilepsy and its relationship with alertness

Abstract: BackgroundTo date, no functional MRI (fMRI) studies have focused on brain entropy in right temporal lobe epilepsy (rTLE) patients. Here, we characterized brain entropy (BEN) alterations in patients with rTLE using resting‐state functional MRI(rs‐fMRI) and explored the relationship between BEN and alertness.MethodThirty‐one rTLE patients and 33 controls underwent MRI scanning to investigate differences in BEN and resting‐state functional connectivity (rs‐FC) in regions of interest (ROIs) between patients and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…rITG (44). Consistently, another DTI-based study of 67 chronic left hemisphere stroke survivors revealed distinct damage in the ITG and MTG among individuals experiencing word comprehension difficulties, suggesting that these regions play an important role in the integration of auditory and conceptual processing (45).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…rITG (44). Consistently, another DTI-based study of 67 chronic left hemisphere stroke survivors revealed distinct damage in the ITG and MTG among individuals experiencing word comprehension difficulties, suggesting that these regions play an important role in the integration of auditory and conceptual processing (45).…”
Section: Discussionsupporting
confidence: 54%
“…In a previous study assessing alertness in unilateral patients with TLE, similar bilateral reductions in VMHC values in the MTG were reported in study subjects ( 28 ). Moreover, resting-state brain entropy analyses in patients with rTLE and the assessment of the relationship between these results, and alertness revealed synchronous alterations in the rMTG and rITG ( 44 ). Consistently, another DTI-based study of 67 chronic left hemisphere stroke survivors revealed distinct damage in the ITG and MTG among individuals experiencing word comprehension difficulties, suggesting that these regions play an important role in the integration of auditory and conceptual processing ( 45 ).…”
Section: Discussionmentioning
confidence: 98%
“…This study has some limitations. Firstly, as obtaining a large dataset is difficult in neuroimaging, where data acquisition is costly, the sample size of this study is relatively limited, but compared with the sample sizes of previous intergroup comparison studies (Lei et al, 2017 ; Zhou M. et al, 2019 ) and some machine learning articles (Hou et al, 2016 ; Tang et al, 2017 ), the sample size of this study is relatively large. Previous studies (Sun et al, 2018 ; Huang K. et al, 2019 ) have shown that multimodal imaging and clinical indicators can improve the performance of machine learning models.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the mTLE lesions are identified by certain biomarked brain regions including the insula, bilateral cingulate gyrus, and precuneus [4,9,44]. By considering the healthy people as a control, Zhou et al [45] found that the left middle temporal gyrus, right middle frontal gyrus, and the left anterior central gyrus were significantly different in temporal lobe epilepsy by the entropy values of the rfMRI data. In addition, by the anatomical connectivity between the left and right hemispheres in the temporal lobe epilepsy, a different connectivity pattern was observed in the cortical-limbic network and cerebellum [46].…”
Section: Functional Biomarker Of Tlementioning
confidence: 99%